Congenital Scoliosis in Smith–Magenis Syndrome: A Case Report and Review of the Literature. Issue 17 (May 2015) - Li, Zheng; Shen, Jianxiong; Liang, Jinqian; Sheng, Lin
Abstract : Abstract: The Smith–Magenis syndrome (SMS) is a complex and rare congenital condition that is characterized by minor craniofacial anomalies, short stature, sleep disturbances, behavioral, and neurocognitive abnormalities, as well as variable multisystemic manifestations. Little is reported about spinal deformity associated with this syndrome. This study is to present a case of scoliosis occurring in the setting of SMS and explore the possible mechanisms between the 2 diseases. The patient is a 13-year-old Chinese female with congenital scoliosis and Tetralogy of Fallot, mental retardation, obstructive sleep apnea, hypertrophy of tonsil, conductive hearing loss, and agenesis of the epiglottis. An interphase fluorescent in situ hybridization at chromosome 17p11.2 revealed a heterozygous deletion, confirming a molecular diagnosis of SMS. She underwent a posterior correction at thoracic 1-lumbar 1 (T1-L1) levels, using the Moss-SI spinal system. At 6-month follow-up, the patient was clinically pain free and well balanced. Plain radiographs showed solid spine fusion with no loss of correction. Congenital cardiac disease, immunodeficiency, and severe behavioral problems can affect the surgical outcome following spine fusion and need to be taken into consideration for the surgeon and anesthesiologist. Scoliosis is not uncommon among patients with SMS, and there is a potential association between congenital scoliosis and SMS. The potential mechanisms in the pathogenesis of congenital scoliosis of SMS included retinoic acid-induced 1 (RAI1) microdeletion and RAI1 gene point mutation.